Leiomyoma and leiomyoma cellulare of the fallopian tube: review of the literature and case reports - L. Sikora-Szczęśniak, Dobrosława (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction: Leiomyoma of the fallopian tube is extremely rare, and its version – leiomyoma cellulare (LC) of the fallopian tube is absolutely unique. Aim of the study was to review literature reports on leiomyomas of the fallopian tubes, and to present cases of leiomyoma and LC of the fallopian tubes in the patients operated on in our ward. Material and methods : There were fewer than 100 cases of leiomyomas of the fallopian tubes discussed in the literature up to 1993. Case 1. Leiomyoma of the left fallopian tube was detected postoperatively in a 68-year-old patient, G.K., on histopathological examination after laparoscopic total hysterectomy with bilateral adnexa.Case 2. A 56-year-old patient, K.T., with LC of the fallopian tube was qualified for laparoscopy. At operation, the procedure was converted to microlaparotomy due to the tumor size. The adnexa on the right side with the tumor of the fallopian tube were excised, and the left fallopian tube was excised, too. Histopathological microscopy found leiomyoma cellulare partim epithelioides. Results: In the presented cases, the extent of operation was connected with the clinical picture, and in the case of LC of the right fallopian tube, with intraoperative histopathological findings. In both cases the postoperative course was uneventful. Conclusions : Diagnosis of leiomyoma and LC of the fallopian tube, like in the other organs of the female genital tract, is possible only due to results of histopathological microscopy.